Institutional Responses to Digital Religious Authority : Muslim Organizations’ Digital Da‘wah Strategies in Navigating Platform Culture in Indonesia - Zaman, Wahyu; Ahmad, Nur; Zakkiyah, Nur (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2026)
This article examines how Nahdlatul Ulama (NU) responds institutionally to the rise of digital religious authority in Indonesia’s platform-based media environment. The study addresses the growing challenge faced by Islamic organizations as religious legitimacy is increasingly shaped by visibility, engagement, and platform culture rather than solely by traditional institutional authority. Using a qualitative-descriptive approach, this research employs digital trace observation of NU’s official websites, social media accounts, video channels, digital services, and publicly accessible organizational documents. The findings show that NU responds through three interconnected strategies: strengthening official digital media, developing institutional digital infrastructure, and enhancing internal digital capacity through content and leadership initiatives. These strategies indicate that NU is not merely adapting to digital change, but is institutionalizing digital da‘wah as a form of authority management. This study argues that digital religious authority has become a strategic organizational issue, requiring Islamic institutions to integrate legitimacy, media management, and platform adaptation.